Assessment of risk factors for kidney disease in an unselected population of nigerians: a report of the routine screening conducted during the national kidney disease awareness and sensitizing programme. (2006)
To be able to define some risk factors for renal disease in an unselected population of Nigerians the Nigerian Association of Nephrology conducted a screening exercise during the National Kidney Disease Awareness and Sensitization Programme whose theme was “Renal Disease in Nigeria: Taming the Lion” which was held at the capital city of Abuja on the 9th of February 2006. A total of unselected 129 respondents who consented were screened. One hundred and nine (56 male and 72 female respondents) were analyzed and the others [2] could not be analyzed because of incomplete data. The mean age of respondents was 27.03 (±10.75) years and majority (89.1 %), were in age group 15 to 44 years with no sex preference. Most of the respondents had normal BMI, the mean being 23.32 (±4.52)mg/m2. More females than males were found to be obese (16% versus 4%), the difference was not statistically significant (p=0.76). A relatively high percentage of respondents gave positive family history of hypertension (40%) as against 25% for diabetes mellitus. Only 5% of respondents gave positive history of renal disease. Use of nephrotoxic agents - medicated soap, native medication and herbal supplements/tea was found in 40%, 30% and 19% respectively. More than half of the studied population did not have routine medical check and about a third engaged in self medication. The prevalence of hypertension and proteinuria were 13.6% and 19% respectively. It is concluded from this study that the risk factors for development of chronic kidney disease (CKD) is high in the studied population and the level of awareness regarding need for routine medical check and appropriate attitude to health low. There is crying need for more intensive, aggressive and comprehensive education aimed at increasing the health seeking attitude of our population as well as establishment of preventive programmes against CKD in the country.